2003
DOI: 10.1081/cnv-120016404
|View full text |Cite
|
Sign up to set email alerts
|

DNA Biomarkers Antecede Semiquantitative Anthracycline Cardiomyopathy

Abstract: Adriamycin (ADM, or doxorubicin hydrochloride) is an effective antineoplastic agent whose use is restricted by its well-described, dose-dependent cardiotoxicity. This study measures ADM DNA adduct formation by 32P-radiolabeling DNA, enzymatically digesting radiolabeled DNA, separating the formed adducts on two-dimensional thinlayer chromatography (2D-TLC), and quantitating the adducts with autoradiography and densitometry. Thirty-six male Sprague-Dawley rats are randomized to receive ADM at varying intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Quantification of ADR-DNA adducts formation by 32 P-radiolabeled DNA has been demonstrated to be an early marker of ADR-induced cardiotoxicity (Hahm et al, 2003). Histological and ultrastructural studies have shown alterations in nucleoli after treatment with ADR, including nucleolar segregation, nucleolar fragmentation, and conversion of nucleoli to a ring shape (Merski et al, 1976(Merski et al, , 1978.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Quantification of ADR-DNA adducts formation by 32 P-radiolabeled DNA has been demonstrated to be an early marker of ADR-induced cardiotoxicity (Hahm et al, 2003). Histological and ultrastructural studies have shown alterations in nucleoli after treatment with ADR, including nucleolar segregation, nucleolar fragmentation, and conversion of nucleoli to a ring shape (Merski et al, 1976(Merski et al, , 1978.…”
Section: Introductionmentioning
confidence: 97%
“…ADR has been demonstrated to exert a multiplicity of effects on myocardial nuclei. Quantification of ADR-DNA adducts formation by 32 P-radiolabeled DNA has been demonstrated to be an early marker of ADR-induced cardiotoxicity (Hahm et al, 2003). Histological and ultrastructural studies have shown alterations in nucleoli after treatment with Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, many other predictive biomarker strategies are currently being developed in the preclinical arena. Proteomics 144 and metabolomics 145 pattern diagnostics, as well as transcriptome profiling 146 , have been shown to be useful in animal models of AIC as well as the detection of doxorubicin DNA adducts (HM-dUMP, 8-OH-dGMP, HM-dCMP, and Me-dCMP) 136 and other particular genes that are overexpressed during incipient cardiotoxicity 137 . Cellular proteins such as S100A1 141 , cMLC1 142 , and cathepsin B 143 have also been shown to have predictive value.…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…Depurination of dGMP and dAMP occurs in parallel with increasing ADM concentration, enabling the quantification of the formed DNA adducts even at low doses of doxorubicin. 60 It is conceivable that analysis from more accessible tissue (e.g., skeletal muscle lymph nodes) surrogating doxorubicin-exposed myocardium may make this diagnostic approach feasible in the near future, but its predictive value remains to be determined.…”
Section: Proteomics/genomics Under Investigation To Search For Novel mentioning
confidence: 99%